Arsenic and Heavy Metals Contamination of Soils Around Oyu Tolgoi and Tavan Tolgoi Mines, Located in The South Gobi Desert of Mongolia - Ragchaa, Galbadrakh; Enkhbat, Temujin; Lkhamsuren, Enkhtor (International Journal of Engineering and Technology, 2018)
In this work inductively coupled plasma - mass spectrometry (ICP-MS) method was used to determine content of harmful to human health heavy elements such as As, Cd, Cr, Pb, Th, U, and other essential elements Zn, Cu, Ni in soil samples collected around fence of two largest in Asia copper (Oyu Tolgoi) and coal (Tavan Tolgoi) deposits. The analyses revealed average content of arsenic in the examined soil samples is exceeding 1.4 times the maximum permissible limit. It is consistent with many previous studies emphasizing on a high occurrence of arsenic in soils, well waters of North and Central Mongolia. But the contents of copper in soil samples collected from three leeward locations of the copper mine Oyu Tolgoi are up to 2.18 times higher than the maximum permitted content established by the government standard of Mongolia. The contents of Cd, Ni, Pb, U, and Zn in soil probes collected from leeward locations of Ukhaa Khudag open pit mine of Tavan Tolgoi coal deposit are higher than that of in probes collected from the windward side of that by factor ranging from 1.34 to 1.64. These facts indicate possible transport and spread of heavy elements by wind from these intense operating open pit mines into adjacent dry and windy deserted region of Mongolia.Â Â